How Investor Sentiment and Trading Behavior affect Stocks Return: : Analyzing from Taiwan Index Series that Traded on The Main Market - Asa Rembokowati, Ni (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This research concerns how investor sentiment and trading behavior affect stock returs while applied in the different conditions from the same sample stocks. This research uses the daily stock price, the number of shares, and trading volumes of the company that includes in Taiwan 50 index on the study period 2016 to 2020. Then from 50 companies listed during the sample period, the researcher excludes those suffering from the suspension of trading or administrative issues, which leaves 43 companies, then the researcher tries to regrouping the samples into several categories. First, is all sample stocks from the 50 index series. Second, regrouping all sample stocks into three group sectors includes electronic, finance, and traditional sectors. Third, the researcher categorizes the same sample stocks into high, middle, and low foreign shareholding. The method of this quantitative causality research is multiple linear regression (MLR). Meanwhile, based on the research results it can be concluded that a large market capitalization on the criteria for grouping a company, can’t be the only standard in determining the influence between variables, because there are other factors that can affect the results of the study.